P195 Domiciliary noninvasive ventilation reduces re-admissions in persistent hypercapnic respiratory failure due to COPD, but are we missing a trick?. (12th November 2019) - Ehilawa, PI; Chisanga, B; Smith, P; Holt, R; Colt, JA; Sovani, MP
Abstract : Introduction and objectives: It is well established that domiciliary noninvasive ventilation (NIV) improves mortality in neuromuscular disease (NMD) patients but evidence for chronic obstructive pulmonary disease (COPD) remains inconclusive. Research has shown reduction in hospital admission in COPD patients with persistent type 2 respiratory failure (T2RF), but variability in clinical practice exists and evidence of outcomes in real-world patients is needed. Methods: We conducted a three-year retrospective study of patients on domiciliary NIV between January 2016 and December 2018. Results: During this period, 220 patients were established on domiciliary NIV; 56% inpatient and 44% outpatient. The underlying diagnoses included; NMD (32%); Obesity Hypoventilation Syndrome [(OHS) (24%)]; COPD (17%); COPD/OHS Overlap (15%); Kyphoscoliosis (6%) and 'Others' (6%). Unlike NMD, COPD (21%), COPD overlap (17%) and OHS (36%) accounted for 74% (n=123) of domiciliary NIV initiated on inpatient admissions. COPD and OHS cohorts had higher median carbon dioxide (PaCO2) levels; COPD [PaCO2 7.72kPa (IQR 6.95–8.96)] and OHS [PaCO2 7.88kPa (IQR 6.71–8.28)]. Only 13% (n=3) of COPD and 7% (n=1) of COPD overlap patients returned their machines due to poor tolerance. The COPD cohort had the highest number of admissions one year prior to NIV initiation, median 2.5 (IQR, 1.25–3) which reduced to 0.5 (IQR 0–2) in the year post NIV. Median Body Mass Index (BMI) was 29 kg/m 2 (IQR 21–31.25) for COPD, 38 kg/m 2 (IQR, 42–48) for COPD overlap and 45 kg/m 2 (IQR 41–52) for OHS cohorts. There were 56 deaths during this period; with highest mortalities in NMD (46%), COPD (23%) and OHS (13%). COPD overlap cohort unexpectedly had the longest median time [17.21 months (IQR 6.3–25)] between NIV initiation and death while OHS cohort had the shortest [4.82 (IQR 3.51–20.75]; suggesting that obesity may have some protective effect but not at extremes. Conclusions: NIV was well accepted and effective in reducing admissions in COPD patients with persistent T2RF. This study raises questions about whether COPD patients should be more closely monitored and proactively initiated on domiciliary NIV as outpatients to reduce readmissions. Importantly, 13% of deaths were from OHS patients, highlighting the need for early intervention in patients with morbid obesity.